Think tanks and the pressures for planning reform in England - Haughton, Graham; Allmendinger, Phil (Environment & Planning C: Government & Policy, 2016)
This article examines how advocacy think tanks have sought to influence the remaking of the English planning system. Pressure for planning reform has come particularly though not exclusively from the political right, which has sought to portray planning as a form of bureaucratic regulation, out of touch with the needs of modern, global economies and the needs of society. This research involved 27 interviewees, the majority of whom have worked in think tanks, whilst others worked in government or in advocacy and professional groups. We explore how despite years of critique and many reforms to the planning system, it is still portrayed as failing. Drawing on ideas around the experimental state, we seek to develop a better understanding of the dynamics behind the process of continuous calls for planning reform before turning to some of the implications for both planning and our understanding of how think tanks seek to influence policy.
Geography
Keywords: advocacy groups; environmental protection planning; experimental state; markets; planning reform; political reform; research institutes; think tanks

Toward a Polanyian network analysis: market and non-market forms of coordination in the rice economy of Vietnam - Prota, Laura (Journal of Economic Geography, 2016)
The study proposes a network-based methodology linking Polanyi's ideal types of coordination and deductive blockmodeling to identify different forms of coordination within an economy. Using the proposed methodology, the economy of rice in postsocialist Vietnam is interpreted as a double movement responding to market liberalization. Qualitative and relational data were collected from 323 households and firms in two communes of the Mekong River Delta of Vietnam. Results show that in one case markets and redistribution co-existed as competing forms of coordination, entailing different relations of production and labor conditions; while in the other they blended and constituted a hybrid house-holding system.
Geography
Keywords: Vietnam; Vietnam transition; blockmodeling; corporate governance; economic coordination; embeddedness; liberalization (finance); local governance; markets; networks; rice - economic aspects; social networks

Embeddedness and migrant tourism entrepreneurs: A Polanyian perspective - Su, Xiaobo; Chen, Zhigang (Environment and Planning A, 2016)
Tourism embodies flows of tourists, capital and information, as well as migration, including migrants who operate businesses. How do migrant entrepreneurs negotiate social ties and economic activities in their destinations? To answer this question, the paper draws on Polanyi’s work on embeddedness to explore migrant tourism entrepreneurs (MTEs) and their modes of integration in the practice of social and economic life. We argue that MTEs are situated in a complex matrix in which they must build economic connections with locals and government officials, yet maintain a respectful distance with local groups, and develop embedded ties with other fellow migrants and tourists. Embeddedness, juxtaposed with distance, indicates that in tourist destinations, mixed patterns of economic and social relations significantly influence MTEs’ social and economic life. A Polanyian perspective on embeddedness can provide useful theoretical tenets to understand entrepreneurial activities in a mobile world.
Geography
Keywords: Lijiang ancient town; embeddedness; migrant tourism entrepreneurs; social and economic life; tourism production system

The business of the Anthropocene? Substantivist and diverse economies perspectives on SME engagement in local low carbon transitions - North, Peter (Progress in Human Geography, 2016)
The involvement of private sector actors in low carbon urban transitions is a neglected element of geographical analysis. Drawing on Polanyian, cultural economic geographies and the non-capitalocentric ethics of JK Gibson-Graham’s diverse economies perspective, the paper engages with the wider literature on the engagement of small and medium enterprises (SMEs) in environmental action, corporate social responsibility and low carbon transitions to develop a substantivist account of the contribution of SMEs to local low carbon transitions. The paper argues that, contra formalist economic analyses of economic rationality, SME owners should not be thought of as uncritical profit maximizers but as actors in favour of positive low carbon futures. Thus the paper argues that Polanyian economic geographies and diverse economies perspectives, which rarely speak to each other, can be drawn together, and concludes with suggestions for future research.
Geography
Keywords: Polanyian geographies; carbon offsetting; cultrual geography; diverse economies; environmental protection; local business representation; local economic development; low carbon transitions; small business; social responsibility of business; substantivist

The New Washington Consensus: Millennial Philanthropy and the Making of Global Market Subjects - Mitchell, Katharyne; Sparke, Matthew (Antipode, 2016)
This paper outlines the emergence of a New Washington Consensus associated with leading philanthropies of the new millennium. This emergent development paradigm by no means represents a historic break with the market rationalities of neoliberalism, nor does it represent a radical departure from older models of early 20th century philanthropy. Rather, it is new in its global ambition to foster resilient market subjects for a globalized world; and new in its employment of micro-market transformations to compensate for macro-market failures. Focusing on reforms pioneered by the new philanthropic partnerships in education and global health, the paper indicates how the targets of intervention are identified as communities that have been failed by both governments and markets. The resulting interventions are commonly justified in terms of “return on investment”. But the problems they target keep returning because the underlying causes of failure are left unaddressed.
Geography
Keywords: development; education; global health; millennial philanthropy; neoliberalism; philanthropy; triple movement

For real: land as capital and commodity - Christophers, Brett (Transactions of the Institute of British Geographers, 2016)
With the aim of helping to revivify a stalled geographical literature on the place of land in capitalist political economies, this article presents a critique of the popular idea that land can be usefully conceptualised as a ‘fictitious’ form of capital or commodity. The critique is based primarily on a close and critical consideration of the grounds on which the identifiers and theorists of such fictitiousness – Marx/Harvey in the case of capital, Polanyi in the case of the commodity – distinguished it from ‘real’ variants. Those grounds, the article argues, are tenuous. And, far from disabling us, treating land as no more or less real than other forms of capital and commodity can empower us in productively revisiting and centring the question of land's political economy – a crucial undertaking in a world where the materiality of land to social relations is writ increasingly large.
Geography
Keywords: MARX; Karl; 1818-1883; capitalism; economic geography; fictitious capital; fictitious commodities; fictitious commodity; land; political economy; social economy

Polanyian Pathways: A review of The Power of Market Fundamentalism: Karl Polanyi’s Critique by Fred Block and Margaret R. Somers and For a New West: Essays, 1919–1958 by Karl Polanyi; edited by Giorgio Resta and Mariavittoria Catanzariti - Peck, Jamie (Economic Geography, 2016)
Geography
Keywords: BLOCK; Fred; CATANZARITI; Mariavittoria; For a New West: Essays 1919-1958 (Book); POLANYI; Karl; 1886-1964; RESTA; Giorgio; SOMERS; Margaret R.; The Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); book review; nonfiction

Countermovement, Neoliberal Platoon, or Re-Gifting Depot? Understanding Decommodification in US Food Banks - Lindenbaum, John (Antipode, 2016)
In this paper, I explore the decommodification that takes place in US food banks. I argue that food banks are neither Polanyian countermovements re-embedding the market in society nor tiny platoons of neoliberalism that advance market relations and state withdrawal. Rather, food banks are best understood as re-gifting depots that are part of the capital accumulation process. Recent scholarship on primitive accumulation, the disarticulations approach, and waste suggests that the devaluation of food products and the exclusion of human labor are everyday elements of capitalism. I conclude by examining the potential for progressive politics in US food banking.
Geography
Keywords: Polanyi - political & social views; Supplemental Nutrition Assistance Program (U.S.); United States Deptartment of Agriculture; commodification; decommodification; disarticulation; equality - social aspects; food banks; food security; primitive accumulation; re-gifting depot; waste

Organic farm volunteer tourism as social movement participation: a Polanyian political economy analysis of World Wide Opportunities on Organic Farms (WWOOF) in Hawai‘i - Mostafanezhad, Mary (Journal of Sustainable Tourism, 2016)
In recent years, Karl Polanyi's concept of the “double movement” has been resurrected to describe growing international resistance to neoliberal global capitalism. The double movement originally referred to counter-movements for social protection against the 19th and early 20th century laissez-faire market. Today, it describes the growth of new social movements which often resist neoliberal economic practices and ideologies. Drawing on Polanyi's concept of the double movement and on recent work on neoliberalism and new social movements, this article examines farm hosts' motivations for participation in World Wide Opportunities on Organic Farms (WWOOF). It argues that farm hosts tend to articulate their motivations as an attempt to proclaim solidarity with organic, spiritual, and educational new social movement agendas. It describes how a loosely articulated organic identity converges around three corollaryprotective counter-movements: organic food production and consumption, spirituality, and alternative education, exploring the creative ways people are resisting neoliberal capitalism at the intersection of alternative tourism and organic agriculture. Yet, despite hosts' intentions, the article illustrates how new social movement participation through WWOOF is in constant tension with the neoliberal agrarian and tourism marketplace in which it operates, as well as the perhaps unforeseen limits of its radical horizon.
Geography
Keywords: POLANYI; Karl; 1886-1964; agri-tourism; capitalism; critical theory; culture change; farm tourism; geography; neoliberalism; organic farming; sustainability; sustainable tourism; volunteer tourism

Local Embeddedness - Pickles, John (International Encyclopedia of Geography: People, the Earth, Environment and Technology, 2016)
In economic geography and economic sociology, embeddedness refers to the ways in which relational, institutional, and cultural contexts shape economic life. In contrast to the undersocialized and utilitarian assumptions of neoclassical economics, rational choice theory, and new institutional economics, theories of embeddedness focus on the ways in which markets and society are variously articulated in particular societies, organizations, and places. Embeddedness in this sense is associated first and foremost with the work of Karl Polanyi. Polanyi argued that the market generally sought to disembed itself from social regulation, while society responded by attempting to socialize and regulate (re-embed) the excesses of unregulated markets. It is also associated with the work of Granovetter in economic sociology, who cautioned against oversocializing, as well as undersocializing, the economy, in favor of a much more detailed analysis of the specific ways in which social relations structured economic practices.
Geography; Sociology
Keywords: POLANYI; Karl; 1886-1964; culture; economy; embeddedness; institutions; society; undersocialized